Basketball : score with STEM! - Kelley, K. C. (Sports STEM., 2022)
"A basketball player speeds down the court toward the basket. With just seconds left in the game the ball leaves their fingertips and arcs its way through the air. Swish! Nothing but net! A good shot takes skill, practice, and a little bit of STEM. Explore the science, technology, engineering, and math behind the game of basketball. Sports and STEM? Score!"--